Global existence and general decay of solutions for a wave equation with memory, fractional boundary damping terms and logarithmic non-linearity - Brahim M.S.T.; Doudi N.; Guefaifia R.; Jan R.; Alharbi R.; Boulaaras S. (Elsevier B.V., 2025)
This study examines the general decomposition and global existence of solutions of the nonlinear wave equation, considering the incorporation of fractional derivative boundary conditions and memory components. ? 2024 The Author(s)